Biological Applications of Short Wavelength Microscopy Based on Compact, Laser-Produced Gas-Puff Plasma Source - Alfio Torrisi; Przemysław W. Wachulak; Andrzej Bartnik; Łukasz Węgrzyński; Tomasz Fok; Henryk Fiedorowicz (Applied Sciences, 2020)
Over the last decades, remarkable efforts have been made to improve the resolution in photon-based microscopes. The employment of compact sources based on table-top laser-produced soft X-ray (SXR) in the “water window” spectral range (λ = 2.3–4.4 nm) and extreme ultraviolet (EUV) plasma allowed to overcome the limitations imposed by large facilities, such as synchrotrons and X-ray free electron lasers (XFEL), because of their high complexity, costs, and limited user access. A laser-plasma double stream gas-puff target source represents a powerful tool for microscopy operating in transmission mode, significantly improving the spatial resolution into the nanometric scale, comparing to the traditional visible light (optical) microscopes. Such an approach allows generating the plasma efficiently, without debris, providing a high flux of EUV and SXR photons. In this review, we present the development and optimization of desktop imaging systems: a EUV and an SXR full field microscope, allowing to achieve a sub-50 nm spatial resolution with short exposure time and an SXR contact microscope, capable to resolve internal structures in a thin layer of sensitive photoresist. Details about the source, as well as imaging results for biological applications, will be presented and discussed.